2011
DOI: 10.1063/1.3666042
|View full text |Cite
|
Sign up to set email alerts
|

Gd plasma source modeling at 6.7 nm for future lithography

Abstract: Plasmas containing gadolinium have been proposed as sources for next generation lithography at 6.x nm. To determine the optimum plasma conditions, atomic structure calculations have been performed for Gd11+ to Gd27+ ions which showed that n = 4 − n = 4 resonance transitions overlap in the 6.5–7.0 nm region. Plasma modeling calculations, assuming collisional-radiative equilibrium, predict that the optimum temperature for an optically thin plasma is close to 110 eV and that maximum intensity occurs at 6.76 nm un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…The precise value of x is yet to be determined but will be decided by the source and reflectivity combination that provides the brightest in-band EUV yield and conversion efficiency. Recent theoretical work has proposed 6.76 nm as the optimum choice for the location of the reflectivity peak of EUV optics in a future lithography system based on the fact that the strongest lines observed in this region originate from Ag-and Pd-like ions [1][2][3]. Previous experimental work [4][5][6] has shown the spectral and in-band intensity dependence of Gd plasmas on laser wavelength, intensity and target composition and concentration.…”
mentioning
confidence: 99%
“…The precise value of x is yet to be determined but will be decided by the source and reflectivity combination that provides the brightest in-band EUV yield and conversion efficiency. Recent theoretical work has proposed 6.76 nm as the optimum choice for the location of the reflectivity peak of EUV optics in a future lithography system based on the fact that the strongest lines observed in this region originate from Ag-and Pd-like ions [1][2][3]. Previous experimental work [4][5][6] has shown the spectral and in-band intensity dependence of Gd plasmas on laser wavelength, intensity and target composition and concentration.…”
mentioning
confidence: 99%
“…The optimum electron temperature of a Gd plasma optimized for 6.7 nm emission is 3 times higher than that required to optimize a Sn plasma for 13.5 nm emission. The plasma expansion velocity is also larger as a result of this higher electron temperature, which, from theoretical modeling, has been calculated to be above 100 eV [2,21]. To limit the etendue, the plasma source size should be controlled by producing a small focal spot and shorter pulse duration in the LPP process.…”
mentioning
confidence: 99%
“…This suggests that the calculation of the ionization balance as a function of the density and temperature of the plasma using a collisional radiative (CR) model is indispensable for the development and application of short-wavelength EUV sources. However, in previous works, 7,8 only a simple model was used, in which only the ground state of each ion was taken into account. 9 It was shown that the CR model of W for fusion plasmas may become very complex, with more than 10 3 excited states of each ion, 10 including the excited states that have a significant population and contribute to EUV emission as well as those that contribute to dielectronic recombination in the calculation of the ionization balance.…”
Section: Nm To the Water Window © 2016 Author(s) All Article Contenmentioning
confidence: 99%
“…5 The emission at λ = 6.x nm from Gd and Tb 6 is considered a candidate source for future microlithography. 7 Light sources at the waterwindow wavelengths, λ = 2.4 -4.5 nm, have attracted attention for biological imaging. 8 However, the temperature of the plasma, and thus the required pumping power, is expected to increase as the wavelength of the UTA decreases because a much greater energy is needed to ionize the target atom to the Pd-like ion.…”
Section: Nm To the Water Window © 2016 Author(s) All Article Contenmentioning
confidence: 99%